REKOMENDASI PERIZINAN MENARA TELEKOMUNIKASI - Hamirul (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
In this industrial revolution 4.0 era, the flow of information has become a necessity for everyone in terms of the use of technology, especially telecommunications with descriptive methods and qualitative approaches. Data collection techniques using interviews with informants as many as 7 people. Research Results The recommendation process for the establishment of telecommunications towers refers to the Republic of Indonesia Minister of Communication and Information Technology Number: 02 / PER / M.KOMINFO / 3/2008 concerning Development Guidelines and Use of Joint Telecommunication Towers. While the requirements for obtaining the license to establish a telecommunications tower are regulated by the Bungo District Regulation Number 19 of 2008 concerning Buildings and Building Construction Permit articles 2 paragraph (2) letter (e). The obstacle faced by the Bungo District Transportation and Information Communication Department in processing the recommendations for Licensing of the Establishment of Telecommunication Towers in Meeting the Order of Government Administration is the Limitations of Human Resources. The efforts made by the Bungo Regency Communication and Information Agency in overcoming obstacles The process of licensing recommendation for the establishment of telecommunication towers in fulfilling the order of government administration is to carry out cross-sectoral cooperation